Safety integrated with quality management as operational excellence tool in the aviation fuel industry - Adekitan, Aderibigbe Israel (Array, 2020)
Factors such as aircraft design, air traffic control, aviation fuel quality, management policies, etc. are associated with flight safety. Diverse methodologies and systems have been developed for managing these intricate factors. Much focus over time has been on the aircraft itself; the design, pre-flight checks and operational procedures. This study is focused on highlighting how the combination of Safety Management Systems (SMS) and Quality Management Systems (QMS) are deployed in the jet fuel value chain for ensuring the safety of personnel, the integrity of the work process and facility and ultimately the supply of quality and dry on-spec Jet A-1 fuel for into-plane or fuelling operations. For the integrated safety and quality management system (ISQMS) to be effective, all stakeholders must play active roles and show utmost commitment to the ISQMS vision and goals. The management of the fuelling company sets the ISQMS pace and drives the process. The ISQMS incorporates all aspect of the business operations and offers both direct and indirect benefits to the business.